Functional Features and Current Applications of the RNA‐Targeting Type VI CRISPR‐Cas Systems. Issue 13 (5th May 2021) - Perčulija, Vanja; Lin, Jinying; Zhang, Bo; Ouyang, Songying
Abstract: CRISPR‐Cas systems are a form of prokaryotic adaptive immunity that employs RNA‐guided endonucleases (Cas effectors) to cleave foreign genetic elements. Due to their simplicity, targeting programmability, and efficiency, single‐effector CRISPR‐Cas systems have great potential for application in research, biotechnology, and therapeutics. While DNA‐targeting Cas effectors such as Cas9 and Cas12a have become indispensable tools for genome editing in the past decade, the more recent discovery of RNA‐targeting CRISPR‐Cas systems has opened the door for implementation of CRISPR‐Cas technology in RNA manipulation. With an increasing number of studies reporting their application in transcriptome engineering, viral interference, nucleic acid detection, and RNA imaging, type VI CRISPR‐Cas systems and the associated Cas13 effectors particularly hold promise as RNA‐targeting or RNA‐binding tools. However, even though previous structural and biochemical characterization provided a firm basis for leveraging type VI CRISPR‐Cas systems into such tools, the lack of comprehension of certain mechanisms underlying their functions hinders more sophisticated and conventional use. This review will summarize current knowledge on structural and mechanistic properties of type VI CRISPR‐Cas systems, give an overview on the reported applications, and discuss functional features that need further investigation in order to improve performance of Cas13‐based tools. Abstract : Class 2 type VI CRISPR‐Cas systems are characterized by Cas13 effector proteins that exclusively cleave single‐stranded RNA. This review article summarizes current knowledge on structural and mechanistic properties of type VI CRISPR‐Cas systems, gives an overview on reported applications of Cas13‐based tools, and discusses functional features that need further investigation in order to improve their performance.